Explore BrainMass

Explore BrainMass

    Solve the Recurrence and Find the Asymptotic Bound

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    1. Solve the recurrence exactly and prove your solution is correct by induction.

    T(1) = 1 , T(n) = 2T(n-1)+2n-1
    T(1) = 1, T(n) = T(n-1)+3n-3

    2. Give asymptotic bound for the following:

    T(n) = 9T(n/3)+n2
    T(n) = T(Sqrt(n))+1.

    © BrainMass Inc. brainmass.com October 9, 2019, 4:55 pm ad1c9bdddf

    Solution Summary

    A recurrence is solved and an asymptotic bound is found. The solution is detailed and well presented.